Faithful of heart [large type] - Peterson, Tracie (Minnesota legacy, 2026)
When dedicated philanthropist Judith Stanford receives a summons from her estranged grandfather ordering her to come to Minneapolis to prove herself worthy of his inheritance, she is hesitant but can't ignore the potential of her grandfather's fortune to benefit her causes. And the only man to interest her since her husband's death lives in Minneapolis, leaving her hoping their paths will cross. Roman Turner, a local physician with a heart for the poor, harbors a grudge against Judith's grandfather. Years ago, his unethical actions ruined Roman's family forever. When Roman meets Judith again, he is shocked to learn the woman he's thought about all these years is related to the one man he can't forgive. As Judith tries to overcome the complicated history between the two families and disentangle her grandfather's tainted legacy, she begins to form a plan for reparation. But when it becomes clear someone else has nefarious intentions for the money, Judith's dreams of a new legacy are at risk.